Inheritance of resistance to common bacterial blight (xanthomonas campestris pv. phaseoli) disease and yield of common bean - Divage, Belarmino (Makerere University, 2015)
The common bean (Phaseolus vulgaris L.) is a legume grain crop with great importance in East Africa, being a source of food and income for most rural households. In Uganda, common bean is a major source of food security being a readily available and popular food to both the urban and rural population. However, productivity of the crop is limited by many diseases, common bacterial blight (CBB) caused by Xanthomonas campestris pv phaseoli (Xcp) being one of them. The use of natural resistance to CBB is the most effective and environmentally sound approach among others to control this disease. This study aimed at i) identifying new resistance genes to CBB and ii) understanding the mode of inheritance in the newly identified sources of resistance. Eighty genotypes (65 lines from the PABRA regional nutritional nursery, 10 interspecific lines (P. coccineus x P. vulgaris) coded ALB, five docummented sources of CBB resistances coded VAX and 24 newly developed resistance lines coded ACC were screened for CBB resistance in a screen house at CIAT Uganda. A Fuscans (Xcpf ) variant of Xanthomonas campestris pv. phaseoli (Xcp ) isolate named “Kawempe 1” was used. From the screening, six genotypes namely JESCA, RWV 2070, RWR 2154, MIB 456, NUA 45 and MCM 2001 were found to have good resistance to CBB. To determine the mode of inheritance of the identified resistance in these six genotypes, crosses with locally prefered genotypes were made, two landraces; Masindi Yellow (large seeded yellow) and Kanyebwa (medium sized red speckled sugar bean), and two released varieties; K131 (small seeded carioca seed type) and K132 (large seeded red mottled) using North Carolina Design II matting design. All the F1 seed available was planted and F1 progenies were advanced to F2 generations in screen house and evaluated for resistance to Xcp using Xanthomonas campestris pv. phaseoli var.Fuscans (Xcpf ) variant of Xanthomonas Campestris pv. phaseoli (Xcp ) ―Kawempe 1‖ . Heritabilities estimates and segregations patterns showed that additive effects predominated over non additive ones with quantitative inheritance. Among the six resistant MCM 2001 and RWV 2070 showed the strongest GCA effect hence most effective resistance. Masindi Yellow X RWR 2070, Kanyebwa x RWR 2070, K 132 x MIB 465, K 131 x JESCA and K 131 x MCM 2001, were considered the most desirable crosses for CBB resistance. The crosses K132 x JESCA, K132 x MIB 456 and Masindi Yellow x RWR 2070 had good mean values for all the yield parameters under analysis. Chi-square tests for goodness of fit showed the presence of more than one gene controlling the resistance to CBB on the materials used on this study. Some of the susceptible parents (K132 and Kanyebwa ) were shown to posses factors contributing to CBB resistance. The heritability estimates for broad-sence and narrow sence coefficient of genetic determination was 0.65 for both, because the SCA variance was negligible due to its negative value, the Bakers ratio was 1, with more than one gene involved with epistatic interaction. From the study findings, it is recommended that the characteristics of resistance to CBB should be investigated in every new parental source when they are initially introduced into the breeding programme. It is also recommended that breeding methods such as crossing and selfing or backcrossing that make the best use of additive variance, should be used to transfer CBB resistance into susceptible commercial and preferred varieties, since the additive gene actions were more important than non-additive gene effects. Generations could also be advanced by the single-seed-descent method or F2-derived families harvested in bulk, due to high hereditability estimation value. Later the promising genotypes should be subjected to multi-location trials to test the stability of their performance while enriching findings regarding their gene action. The promising stable varieties identified should be subjected to selection, preferably with participation of farme